Oral diseases caused by the use of electronic cigarettes: literature review (Research, Society and Development, 2022)
Approximately 90% of people who die from oral cancer are smokers according to the National Cancer Institute, with smoking being one of the main triggers of oral cancer. This work aims to verify the effects of the use of electronic cigarettes (ECs) in the oral cavity, being approached from the main oral alterations observed in these individuals, their occurrence, as well as therapeutic strategies and the role of the dental professional in the education and awareness process. about the risks of using ECs. Data searches were performed in the following databases: SciELO, VHL, PubMed and Google Scholar, with the help of the Rayyan QCRI program in the organization of the selected articles. A total of 60 articles were identified in the databases, 8 of which were included according to the study's eligibility criteria. The use of ECs presents multiple health risks, in addition to damage to oral tissues, head and neck cancer. Therefore, the role of the dental surgeon is essential in the intervention by encouraging the patient to control smoking and performing preventive oral self-examination, in order to detect early signs of lesions in the oral cavity. More studies on this topic are still needed to better understand the effects of the use of ECs in the oral cavity, in addition to alerting the population and bringing new knowledge to dental professionals, with emphasis on the harmful effects of EC in the oral environment.